Impact of COVID-19 on Women Who Are Refugees and Mothering: A Critical Ethnographic Study. (September 2022) - Hirani, Shela Akbar Ali; Wagner, Joan
Refugee women often experience trauma and social disconnection in a new country and are at risk of experiencing reduced physical, mental, and emotional well-being. Globally, COVID-19 has affected the health and well-being of the population at large. This critical ethnographic study aimed to explore the effects of COVID-19 on women who are refugees and mothering in Saskatchewan, Canada. In-depth interviews were undertaken with 27 women who are refugees and mothering young children aged 2 years and under. This study suggests that during COVID-19, refugee women are at high risk of experiencing add-on stressors due to isolation, difficulty in accessing health care, COVID-19-related restrictions in hospitals, limited follow-up care, limited social support, financial difficulties, and compromised nutrition. During COVID-19, collaborative efforts by nurses, other health-care professionals, and governmental and non-governmental organizations are essential to provide need-based mental health support, skills-building programs, nutritional counseling, and follow-up care to this vulnerable group.